2005
DOI: 10.2737/rmrs-gtr-142
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of native species and ungulate grazing in the Southwest: Terrestrial wildlife

Abstract: ______________________________________Range managers in the Southwestern States are increasingly being required to develop management strategies that take into consideration the conservation of wildlife populations. However, information on many aspects of the fundamental biology and impacts of grazing on individual species is still lacking in the scientific and government literature. This report documents a project designed to assemble this information for terrestrial wildlife in Arizona and New Mexico that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In three separate studies, this species was absent from heavily grazed or browsed areas but was found on nearby ungrazed or lightly grazed comparison plots (Berger et al 2001, Medin and Clary 1991, Mosconi and Hutto 1982). The negative impact was considered to be a result of alteration of important vegetation structure and composition, as well as negative impacts on water quality or water regimes that affect vegetation (Zwartjes et al 2005).…”
Section: Grazing-mentioning
confidence: 99%
See 2 more Smart Citations
“…In three separate studies, this species was absent from heavily grazed or browsed areas but was found on nearby ungrazed or lightly grazed comparison plots (Berger et al 2001, Medin and Clary 1991, Mosconi and Hutto 1982). The negative impact was considered to be a result of alteration of important vegetation structure and composition, as well as negative impacts on water quality or water regimes that affect vegetation (Zwartjes et al 2005).…”
Section: Grazing-mentioning
confidence: 99%
“…Livestock grazing may contribute to reduced fire frequency in ponderosa pine forests by reducing the amount of grass that facilitated the spreading of low-intensity fires (Zwartjes et al 2005). The depletion of competing grasses and lack of fire encouraged the growth of shrubs and dense stands of young conifers (Chambers andHolthausen 2000, Touchan et al 1996).…”
Section: Grazing-mentioning
confidence: 99%
See 1 more Smart Citation
“…They increased with snag density, and were most abundant in stands with >3 snags per acre. They were also most abundant in stands with >20% of snags in decay class 2 (Zwartjes et al 2005). Cordilleran Flycatchers prefer cool, well-structured forests with a dense understory (Zwartjes et al 2005) Cordilleran Flycatchers are present in New Mexico from May to September (Parmeter et al 2002).…”
mentioning
confidence: 99%